Thiol-functionalized metal–organic frameworks embedded with chelator-modified magnetite for high-efficiency and recyclable mercury removal in aqueous solutions. Issue 12 (23rd February 2022) - Li, Yuliang; Tan, Mengxi; Liu, Guangxia; Si, Dunfeng; Chen, Ning; Zhou, Dongmei
Abstract : A new adsorbent (Fe3 O4 @DTIM-MOF@SH) for aqueous Hg removal was synthesized. The surface S sites played a dominant role in Hg 2+ capture. The adsorbent showed wide application and recyclability for Hg 2+ adsorption. Abstract : Aqueous mercury (Hg) pollution has aroused increasing concern due to its harmful effects on human health and environmental sustainability. The development of high-efficiency and recyclable adsorbents for Hg removal is of great significance in aqueous environments. Herein, we synthesize a Fe3 O4 @DTIM (4-(5)-imidazoledithiocarboxylic acid)-MOF (metal–organic framework)@SH composite as a high-efficiency and recyclable adsorbent for the removal of Hg 2+ . The typical MOF, known as HKUST-1, modified with Fe3 O4 @DTIM and ethanedithiol endow the material with recyclability and high efficiency, respectively. The optimized Fe3 O4 @DTIM-MOF@SH composite showed high affinity (adsorption rate constant K 1 = 0.29 g mg −1 min −1 ) and adsorption capacity (756.9 mg g −1 ) for aqueous Hg 2+ removal within 120 min. Fe3 O4 @DTIM-MOF@SH can be applied to adsorb Hg 2+ in the pH range of 4.0 to 7.0. Additionally, the adsorbents showed high performance for Hg 2+ adsorption after five cycles of utilization. State-of-the-art characterization and DFT calculations demonstrated that the sulfhydryl group on the Fe3 O4 @DTIM-MOF@SH composite played an important role in Hg 2+ adsorption. Thus, this study provides a new strategy for the development of MOF-based adsorbents for the high-efficiency removal of mercury during remediation activities in aqueous solutions.